2017
DOI: 10.1093/pch/pxx092
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels and influencing predictors in refugee children in Sherbrooke (Quebec), Canada

Abstract: This study concluded that refugee children have insufficient vitamin D levels. Gender, age, latitude and season of testing have an impact in predicting vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
3
1
0
Order By: Relevance
“…In addition, we also found that hypovitaminosis D was prevalent in older children, and infants had the highest level of mean serum 25(OH) D (33.25 ± 13.64 ng/ml). However, childhood vitamin D nutritional status deteriorated with advancing age, which was in line with Korean and Canadian studies [23,24]. Generally, outdoor activities and vitamin D supplementation in children younger than 3 years old depend on parental support, whereas those in school children older than 6 years are limited or encouraged by schools.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, we also found that hypovitaminosis D was prevalent in older children, and infants had the highest level of mean serum 25(OH) D (33.25 ± 13.64 ng/ml). However, childhood vitamin D nutritional status deteriorated with advancing age, which was in line with Korean and Canadian studies [23,24]. Generally, outdoor activities and vitamin D supplementation in children younger than 3 years old depend on parental support, whereas those in school children older than 6 years are limited or encouraged by schools.…”
Section: Discussionsupporting
confidence: 79%
“…This observational study was the rst to assess circulating 25(OH)D in over 50,000 children by HPLC-MS/MS, the current gold standard in vitamin D level assessment [21] . Our data showed that (1) status deteriorated with advancing age, which was in line with Korean and Canadian studies [22,23] .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we also found that hypovitaminosis D was prevalent in older children, and infants had the highest level of mean serum 25(OH)D (33.25±13.64 ng/ml). However, childhood vitamin D nutritional status deteriorated with advancing age, which was in line with Korean and Canadian studies [23,24] . Generally, outdoor activities and vitamin D supplementation in children younger than three years old depend on parental support, whereas those in school children older than six years are limited or encouraged by schools.…”
Section: Discussionsupporting
confidence: 86%